An internet-delivered vak learning style assessment: development, validation, and implications for educational practice in Indonesia - Widyana, Rahma; Sofia Afiati, Nikmah; Sumiharso; Merli Safitri, Ranni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Learning Style VAK Inventory for Junior High School students in Indonesia, addressing the need for culturally relevant, technology-driven assessments. Existing learning style inventories often lack adaptation to specific educational contexts, and there is a growing demand for accessible, internet-based evaluation tools. This study seeks to fill this gap by examining the inventory’s construct validity, reliability, and effectiveness in classifying students’ learning preferences. The inventory, consisting of 15 items measuring visual, auditory, and tactile learning styles, was tested on a sample of 1,400 students using online data collection. Confirmatory Factor Analysis (CFA) was conducted to assess the factor structure, yielding good model fit indices (CFI = 0.946, RMSEA = 0.024, SRMR = 0.027), supporting the inventory’s validity. However, internal consistency was moderate (Cronbach’s Alpha = 0.580), highlighting the need for further refinement. Item discrimination indices ranged from 0.132 to 0.328, suggesting revisions for clarity and relevance. Descriptive findings indicated that tactile learners scored slightly higher (Mean = 21.187) than visual (Mean = 20.872) and auditory learners (Mean = 19.119), reflecting individual differences in learning preferences. While the study confirms the instrument’s structural validity, limitations include moderate reliability and potential biases due to online administration. Future research should focus on improving reliability, refining weak items, and ensuring broader population representation. The findings suggest that this inventory could assist educators in tailoring instructional strategies to students' learning preferences, supporting adaptive curriculum planning and personalized learning approaches in digital education settings.